Crime narratives, dramatizations, and the legacy of the Kitty Genovese murder: a half century of half truths - Lurigio, Arthur J. (Criminal justice and behavior, 2015)
Kitty Genovese's murder in New York City fueled widespread perceptions about the dangers of urban life and contributed to the stereotype of the apathetic American. Gross inaccuracies in the reporting of the story, and a short but sensationalist book written by the editor who commissioned the story, spun an enduring tale of witness indifference and spawned research on the bystander intervention effect. This essay focuses on two books that commemorate the 50th anniversary (2014) of the Genovese case. Written in the true-crime genre, the books are replete with detailed portrayals of the victim and her murderer, as well as his trial and conviction and the impact of the case on American culture. The essay also explores the emerging revisionist perspective on the Genovese incident, which illustrates how the dramatized reportage of the case iconized Kitty and reserved a permanent place for her in crime victim narratives and psychology textbooks.